2018
DOI: 10.11622/smedj.2018011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcome measures from different pathways following total knee arthroplasty

Abstract: Introduction:The benefits of extended inpatient rehabilitation post-total knee arthroplasty

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 67 publications
1
16
0
Order By: Relevance
“…They concluded that older, female and less educated patients with poorer preoperative functional scores were more likely to be discharged to CHs after TKA. At the two-year follow-up, patients in CHs had less improvement in functional outcomes than those discharged home [9,10] .…”
Section: Discussionmentioning
confidence: 91%
“…They concluded that older, female and less educated patients with poorer preoperative functional scores were more likely to be discharged to CHs after TKA. At the two-year follow-up, patients in CHs had less improvement in functional outcomes than those discharged home [9,10] .…”
Section: Discussionmentioning
confidence: 91%
“…In the "Model for Perioperative Orthopaedic Education via Telehealth" section, the EDUCATE principles are utilized to form the content, pace, and mode of instruction for the preoperative and postoperative education that is tailored to the needs of the patient. At discharge, patients encounter different challenges in physical, social, and environmental contexts, leading to unmet educational needs that are specific to their situations (Cano-Plans et al, 2018;Conradsen et al, 2016;Groeneveld et al, 2020;Tilbury et al, 2016) and can lead to poor outcomes (Chan et al, 2018). Patients who have undergone orthopaedic joint replacement surgery may need to travel great distances for quality care, may lack access to transportation, may have limited financial means to leave home, and may be dealing with the effects of pain and limited mobility after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…When other types of orthopaedic conditions are considered, that number is even greater. With any type of orthopaedic surgery, there is a risk of poor outcomes such as pain and decreased mobility (Chan et al, 2018) and decreased function with daily activities (Tilbury et al, 2016). In addition, patients may not be adequately prepared for discharge if they struggle to comprehend or retain information (Causey-Upton et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…1). Of these, four RCTs evaluated novel (hypothesized better) rehabilitation programs versus standard care or alternative rehabilitation programs, 37,40,53,73 four RCTs evaluated comparatively similar rehabilitation programs delivered with varying intensity and/or timing, 46,49,54,85 six studies (3 RCTs, 3 NRCSs) evaluated comparatively similar rehabilitation programs delivered in different settings or by different personnel, 32,35,47,63,64,67 and seven RCTs evaluated comparatively similar rehabilitation programs with or without an adjunctive modality. 28,42,72,78,80,84,86 Acute-phase rehabilitation interventions were initiated inhospital from immediately postop to 2 wks after surgery.…”
Section: Description Of the Acute-phase Rehabilitation For Tka Evidencementioning
confidence: 99%